2019
DOI: 10.1080/15384047.2019.1599660
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer stem cells: Potential target for the treatment of colorectal cancer

Abstract: Despite incessant research, colon cancer still is one of the most common causes of fatalities in both men and women worldwide. Also, nearly 50% of patients with colorectal cancer show tumor recurrence. Recent investigations have highlighted the involvement of colon cancer stem cells (CCSCs) in cancer relapse and chemoresistance. CCSCs deliver a significant protumorigenic niche through persistent overexpression of self-renewal capabilities. Moreover, CSCs cross network with stromal cells, immune infiltrates, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 153 publications
(140 reference statements)
1
100
0
Order By: Relevance
“…Recently, much has been invested to study the host-microbiota interactions, which can explain, with the concept of dysbiosis (i.e., the perturbation of the balance-eubiosis-of the different microbiota populations inhabiting the human gut), the chronic inflammation responsible of carcinogenesis and tumor progression in the colon [39]. However, as similar to what has already been discussed for the other solid cancers, despite the several advances in prevention, diagnosis, and treatment done in the last years for colon cancer, nearly 50% of patients show tumor recurrence, and in this case too, this can be attributed to the presence of CSCs [40].…”
Section: Top Five Lethal Solid Cancerssupporting
confidence: 56%
“…Recently, much has been invested to study the host-microbiota interactions, which can explain, with the concept of dysbiosis (i.e., the perturbation of the balance-eubiosis-of the different microbiota populations inhabiting the human gut), the chronic inflammation responsible of carcinogenesis and tumor progression in the colon [39]. However, as similar to what has already been discussed for the other solid cancers, despite the several advances in prevention, diagnosis, and treatment done in the last years for colon cancer, nearly 50% of patients show tumor recurrence, and in this case too, this can be attributed to the presence of CSCs [40].…”
Section: Top Five Lethal Solid Cancerssupporting
confidence: 56%
“…to maintain the stemness of CSCs. Under specific microenvironmental stimuli, certain cancer cells exhibit plasticity, which enables them to resume proliferation through EMT [121]. For example, Chang et al [122] revealed that the activation of the Hh signaling pathway in the TME can transform common prostate cells into stem cells.…”
Section: Cscs Niche Tme and Drug Resistancementioning
confidence: 99%
“…Colorectal cancer also presents high tumor recurrence of up to 50% [7]. Evidence showed the presence of cancer stem cells with the ability to self-renew and re-form tumors in the colon with added drug resistance [8]. Additionally, CRC exhibits high metastasis rates, where most CRC tumors are diagnosed through detection of a secondary lesions in the liver or lungs, rather than the primary tumor in the colon itself [9].…”
Section: Introductionmentioning
confidence: 99%